Implementación de un prototipo de granja vertical para el control y monitoreo del crecimiento de las plantas, haciendo análisis de imágenes, forma, tamaño y color utilizando internet de las cosas – Ibagué (Tolima) (2021)
The increase in population in the world affects different areas such as food security, occupation of territory, and food security, therefore it makes it mandatory to modify the dynamics of behavior in human beings, the problem can be observed from two points of view, the first corresponds to the union of food security and reduced urban spaces and the second from the implementation and technological integration.